GAMBARAN KEBIASAAN MENGONSUMSI MAKANAN CEPAT SAJI DAN OBESITAS PADA MAHASISWA SEMESTER V PROGRAM STUDI KEDOKTERAN UMUM UNIVERSITAS UDAYANA TAHUN 2014 - Ratih Pradnyandari Pemayun; Ratna Saraswati (Intisari Sains Medis, 2015)
Background : Obesity has been occured by deposit of fat in subcutaneous and intra abdominal tissue. The prevalance of obesity in Indonesian womens were 32,9% and mens is 19,7 % respectively. In general side, the prevalence of obesity in 18 years old adult peoples were 15,4%. The major risk factors for obesity including lifestyle dietary changes such as consuming fast food habit.Â Objective : to find out overview of consuming fast food habit and obesity in medical students.Â Method : This research was cross-sectional decriptive study. The respondens were 127 medical students on 5th semester in Udayana University on 2014. The qualitative data were be measured by questionnaires. The variables were including age, gender, general knowledge of parents, parental income monthy, body mass index (BMI), habit of consuming fast food, average outcome monlty of medical students, and daily frequency of consuming fast food.Result : the characteristic respondens including : a) mostly 20 years old, b).women more than men, c). level education of parents were university, d). monthly parental income more than 5 million rupiah, e). BMI in normal limit, f).degree of obesity were grade I, g).inconvience consuming fast food daily, h).monthy outcome of medical students were aproximately 500.000 rupiah, and i).regular consuming fast food mostly once weekly.Conclusion : mostly responden were women with normaly of BMI and inconvenience consuming fast food daily.Â